#TITLE_ALTERNATIVE# - KAMILA (NIM: 10210043); Tim Pembimbing : Dr. Eng. Alamta Singarimbun; Wahyu Srigutomo Ph.D, GHINA
Modelling of Electromagnetic (EM) field yield from analytical procedure which is developed to obtain the exact evaluation of the complete integral that representation EM field components generated by a Vertical Magnetic Dipole (VMD) lying on the surface of a flat and homogeneous half-space earth. The model of electromagnetic fields build both for homogeneous and layered earth assumption to proof and compare the output at the same resistivity value. At first, models are built in frequency domain formulation. Quasi-static approximation take occasion, which only valid in the low- frequency range, while build forward modelling data. Furthermore, these data will be transformed on to time domain by inverse Fourier transform using quadrature Gauss-Kronrod numerical method.